CHRONIC HEART FAILURE OF ISCHEMIC ORIGIN: ROLE OF CHRONIC PULMONARY OBSTRUCTIVE DISEASE - N. T. Vatutin; A. S. Smyrnova; E. S. Gasendich (Российский кардиологический журнал)
Pathology of cardiovascular and respiratory systems still predominates the structure of morbidity and mortality all over the world. Especially it is important due to continuous senilization of inhabitants and comorbidity, which is characterized by relevant complication of the conditions by each other and serious worsening of prognosis in such patients. Contemporary approaches for therapy of chronic obstructive lung disease and chronic heart failure during last years led to achievement of some success in control of these diseases and improvement of life quality. However in their combinated course there are difficulties in standard therapy application to such kind of patients.